Reading Literacy in Management Study Program STIE Bina Karya - Haratikka, Haya; Purba, Anita; Silitonga, Dwi Handayani (STIE Bina Karya, 2023)
Reading literacy is a crucial skill that empowers individuals to comprehend, analyze, and engage with written information effectively. The importance of reading literacy in both personal and societal contexts highlighted the cognitive and emotional benefits of strong reading skills, including expanded knowledge, critical thinking, and empathy. Additionally, it addresses the essential role of reading literacy in education, career development, and lifelong learning. The informants of this research were 135 college students who represented each semester. The data were analyzed by implementing descriptive qualitative method. The findings were reading literacy of management study program studentsare almost the same with others study programs. They prefer to read e-book rather than purchasing on offline or online bookshop. It found that before the end of the semester the students’ reading percentage were high because they have to finish their task as directed by the lectures. Besides reading e-book rather than purchasing books, library is the best place to read and do discussion whenever they have individual or group task.